1999
DOI: 10.1007/s001270050147
|View full text |Cite
|
Sign up to set email alerts
|

Mental health, "burnout" and job satisfaction in a longitudinal study of mental health staff

Abstract: These results suggested that working in the community may be more stressful than working in in-patient services. However, there was no evidence to suggest that levels of stress are increasing over time, either in community-based or hospital-based staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
2
10

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 8 publications
5
56
2
10
Order By: Relevance
“…Chaplains, like social workers, hold far less prestigious positions than medical staff and thus may be equally prone to burnout in such settings, but the findings are limited (Flannelly et al 2005a, b). In contrast to these findings, Prosser et al (1999) reported that burnout was lower among mental health professionals working in hospital settings compared to those working in community settings.…”
Section: Introductionmentioning
confidence: 58%
“…Chaplains, like social workers, hold far less prestigious positions than medical staff and thus may be equally prone to burnout in such settings, but the findings are limited (Flannelly et al 2005a, b). In contrast to these findings, Prosser et al (1999) reported that burnout was lower among mental health professionals working in hospital settings compared to those working in community settings.…”
Section: Introductionmentioning
confidence: 58%
“…Considering the significantly higher level of cynicism and depersonalization among younger employees found in this study and others it would be prudent for employers to closely monitor the mental state of young workers (Schwartz et al 2007). Several studies have discovered a discrepancy between the preconceived ideas of young child and youth care workers and the reality of child and youth care work (Prosser et al 1999). It could be highly valuable and cathartic for younger employees to have an older, more experienced mentor to discuss feelings of disenchantment, frustration, and emotional detachment.…”
Section: Practical Recommendationsmentioning
confidence: 95%
“…In others the variables of years in the profession and years in current post or setting were reported just as descriptive means rather than reporting of possible correlations (Edwards et al, 2001;Sorgaard et al, 2007). Prosser et al's (1999) modelling of mental ill health and burnout in UK acute and community mental health nurses found correlations between tenure in the profession and burnout factors but not GHQ caseness. Ryan and Quayle (1999) found age (being under 30) but not years of practice to relate to GHQ60 caseness or work stress indicators in Irish psychiatric nurses.…”
Section: Years In the Profession And Years In Rolementioning
confidence: 99%